Fast removal of high quantities of toxic arsenate via cationic p(APTMACl) microgels. (15th January 2016) - Rehman, Saif ur; Siddiq, Mohammed; Al-Lohedan, Hamad; Aktas, Nahit; Sahiner, Mehtap; Demirci, Sahin; Sahiner, Nurettin
Abstract: Hydrogels are resourceful materials and can be prepared in different morphology, size, surface charge and porosity adopting different polymerization techniques and reaction conditions. The cationic poly(3-acrylamidopropyl)trimethylammonium chloride (p(APTMACl)) microgels were synthesized by photo-initiated inverse suspension polymerization technique. These microgels were utilized as absorbents for the removal of toxic arsenate (As) from different aqueous environments. The experimental parameters affecting absorption efficiency were investigated, and it was demonstrated that these types of microgels are highly efficient in removing arsenate anions from different aqueous environments compared to the previously reported bulk hydrogel, and cryogel of the same material. A removal efficiency of approximately 97.25% was obtained by immersing 0.5 g microgel in 250 ppm 100 mL solution of arsenate anions for 60 min. Both Langmuir and Freundlich adsorption isotherms were applied to adsorption of arsenate anions by p(APTMACl) microgels, and the Langmuir isotherm was a better representation of the adsorption of arsenate with a high value of R 2 (0.9982). Furthermore, mag-p(APTMACl) microgels were synthesized for the adsorption of arsenate anions to provide easy removal of the microgel composite by using an externally applied magnetic field. Furthermore, re-usability of the p(APTMACl) microgels was also investigated for the adsorption of arsenate anions. Graphical abstract: Highlights: Cationic p(APTMACl) microgels as effective arsenate adsorbent. Fast (60 min) and high amount (130 mg/g) of arsenate removal by cationic microgels. Magnetic microgel composite adsorbents for easy separation from adsorption media. Arsenate free bottled, tap, creek, sea waters from contaminated sites by microgels.